Examining Knowledge, Skill, Stress, Satisfaction, and Self-Confidence Levels of Nursing Students in Three Different Simulation Modalities - Şengül Üzen Cura; Vildan Kocatepe; Dilek Yıldırım; Hilalnur Küçükakgün; Selma Atay; Vesile Ünver (Elsevier, 2020)
Purpose: The aim of this study was to compare the effect of different simulation modalities on knowledge, skill, stress, satisfaction, and self-confidence levels of students receiving undergraduate education in three nursing schools. Method: This was an experimental study. Students applied the scenario of "Respiratory Sounds Assessment" which was prepared according to three different simulation modalities. In the study, the standardized patient, high-fidelity simulation, and partial task trainer were used as simulation modalities. Results: An increase was observed in postpractice knowledge levels of the three groups which had similar knowledge levels before the practice. Virtual Analog Scale stress levels of the students in the standardized patient group were higher than those of others. The students' mean scores of satisfaction in learning were higher in the standardized patient group. The students in the partial task trainer group had lower scores of self-confidence in learning. Skill scores of the students were lower in the standardized patient practice than those in others. Conclusion: Simulation-based experiences give students the opportunity of experiencing situations they may experience in the actual practice beforehand. Therefore, this may increase their performance in real practices, as reality increases in the standardized patient group.